ATIVIDADE DA NTPDase DE LINFÓCITOS NA DERMATITE DE CONTATO ANTES E APÓS TRATAMENTO COM DEXAMETASONA NANOESTRUTURADA - Brum, Liliani Mathias (2008)
Since the extracellular nucleotides represent an important means of modulating the activity of lymphocytes, it is essential the presence of an enzymatic mechanism to keep constant the concentration of those in the extracellular space. The activity of NTPDase has been recognized as a marker of activation necessary for the function of effector lymphocytes, participate in the processes of recognition of antigen. Contact dermatitis occurs in a delayed hypersensitivity reaction of type IV, mediated by cells through a mechanism that sensitizes the immune T lymphocyte to an antigen protein or a hapten linked to a protein. Among the mediators able to modulate the actions of lymphocytes stand out from the nucleoside and nucleotide adenine, in particular the extracellular ATP that is able to regulate the cell-cell interactions are important processes of activation, differentiation, development, proliferation, cell death and responses of effector lymphocytes. This study sought to determine first of the hydrolysis of adenine nucleotides, the NTPDase (EC 3.6.1.5, nucleoside triphosphate difosfoidrolase, CD39) in lymphocytes from mice with dermatitis induced by nickel sulphate to 5%, before and after treatment with dexamethasone and dexamethasone nanostructured free to try to check the possible changes in the activity of this enzyme front of an inflammatory reaction of type IV hypersensitivity and immunosuppressive therapy. Moreover, it was possible to verify the relationship of submission of the drug in the formulation free and nanostructures with the hydrolysis of adenine nucleotides. The average enzymatic activity of the group with contact dermatitis was significantly higher in the control group by the test of hypotheses to averages T. The results are in line with work done earlier that showed an increase of enzyme activity by the activation of lymphocytes. The hydrolysis of ATP and ADP in the group treated with dexamethasone free and in the group treated with dexamethasone nanostructured was significantly higher in the control group by analysis of variance for a way (ANOVA) followed by Kruskal-Wallis test (P < 0001). The results are in line with work done earlier that showed an increase of enzyme activity by the activation of lymphocytes. Was observed greater hydrolysis of ATP and ADP in the group treated with dexamethasone nanostructures in relation to the group treated with dexamethasone free. However, this difference was not statistically significant. Work previously shown an increase of enzyme activity during treatment with dexamethasone as a possible compensatory effect of the decrease in the number of lymphocytes. The results of this study suggest that dexamethasone nanostructures possess a immunosuppressive effects greatest, which may be the beginning of the evaluation of a more effective and safe treatment for contact dermatitis. From these results we can conclude that the determination of the activity of NTPDase in lymphocytes could be used as an indicator of the efficiency of the treatment of contact dermatitis